A review of research progress on disease burden of foodborne aflatoxins - Mei QIN; Jinyao CHEN; Lishi ZHANG; Jiao HUO; Yang SONG; Li CHENG (Zhongguo gonggong weisheng)
Aflatoxins (AFs) are fungal secondary metabolites that can contaminate various agricultural crops and their derived products, posing a significant global food safety challenge. The International Agency for Research on Cancer (IARC) has classified AFB1, AFB2, AFG1 and AFG2 as Group 1 carcinogens, primarily causing hepatocellular carcinoma (HCC) in humans, but also affecting growth and development in children and damaging the human immune system, resulting in varying degrees of health burden to populations. The World Health Organization published the global burden of foodborne AF in 2015, and several countries and regions have conducted population-based studies on the burden of foodborne AF. This article reviews the progress of foodborne AF disease burden research from 2010 to 2023, providing a foundation for more comprehensive disease burden studies in the future.